Determinants of household electrical energy consumption: Evidences and suggestions with application to Montenegro - Vladimir urišić; Sunčica Rogić; Julija Cerović Smolović; Milena Radonjić (Energy Reports, 2020)
The aim of this paper is to examine various socio-economic, dwelling-related and appliance-related factors which influence electricity consumption in Montenegro. Data was collected via questionnaires completed by 964 households in the second quarter of 2019 in Montenegro. Structural Equation Modelling (SEM) was applied in order to simultaneously examine the causal relationships between multiple factors, using a series of equations. The obtained results indicate the importance of income, dwelling size, family composition and routines, appliance age and region in determining household electricity consumption in Montenegro. The results show that the determinant which influences the electricity bill the most is the dwelling size, followed by the family composition and routines. On average, during winter and summer, dwelling size contributes to the energy consumption with 95%, while family composition and routines contribute with 56.85%. These determinants exert the same influence in winter and in summer, with the only statistically significant difference being observed in the variables that describe the types of heating or cooling.
Keywords: 330; Household electricity consumption; SEM; Montenegro